2016
DOI: 10.1177/1010539515626268
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Immunization and Access to Health Care

Abstract: This article examines the effect of access to health care center, in terms of travel time, on childhood immunization in Nepal using the 2004 and 2011 waves of the Nepal Living Standards Measurement Surveys. We employ probit and instrumental variable probit estimation methods to estimate the causal effect of travel time on the probability of immunization. Results indicate that travel time to the nearest health center displays a significant negative association with the probability of immunization (coefficient =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…Univariate analysis indicated a pronounced decline in coverage of immunisation with increased travel time to health facilities for travel times of greater than an hour. Longer travel time also correlate with other factors such as increased transport costs which may also play a major role in decreased service utilization [ 15 , 19 ]. There was a significant effect on both fully immunised status and DPT3 coverage up to more than two-hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Univariate analysis indicated a pronounced decline in coverage of immunisation with increased travel time to health facilities for travel times of greater than an hour. Longer travel time also correlate with other factors such as increased transport costs which may also play a major role in decreased service utilization [ 15 , 19 ]. There was a significant effect on both fully immunised status and DPT3 coverage up to more than two-hours.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple contacts with health facilities are required to achieve full immunisation status [ 17 ]. However, long distances and increased travel times (spatial accessibility) remains a major barrier to expanding immunisation coverage in many SSA countries [ 15 , 18 , 19 ]. This is more pronounced in the rural areas, where most of the unvaccinated children live and where services are limited [ 20 , 21 ] and in informal settlement that are densely populated and often affected by significant traffic delays [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is because the geographical area that mainly composes of the mountains and hills which require considerable travel time and travel costs. This condition where the increase in costs of travel may significantly reduce the immunization success rate (Devkota & Panda, 2016).…”
Section: The Relationship Between Access Variable and The Advanced Pementioning
confidence: 99%
“…Spatial access to a health facility, especially in sub-Saharan Africa (SSA) countries, is a signi cant determinant of DTP3 vaccination coverage as the vaccine is mainly administered during routine immunisation schedules at health facilities [11][12][13]. Studies have shown that rural areas [14,15] and densely populated informal settlements [16,17] are most affected by poor access to healthcare services.…”
Section: Introductionmentioning
confidence: 99%